MICROHABITAT USE, MORPHOLOGY, AND LIFE CYCLE OF BROWN WIDOW SPIDER LATRODECTUS GEOMETRICUS (A RANEAE: THERIDIIDAE) I N THAILAND: A CASE STUDY OF COMMUNITY HOUSING IN SAMUT SONGKHRAM PROVINCE - T. Chaiphongpachara; A. Lotulit; S. Sumruayphol (Journal of Animal and Plant Sciences, 2019)
The brown widow spider, Latrodectus geometricus Koch 1841, is a toxic spider that is widespread in Thailand, where it has recently been reported on by various media outlets, causing wide concern among the public. However, very little is currently known about the ecology of this species in this country. Therefore, the aim of this research was to investigate the microhabitat use, morphology, and life cycle under laboratory conditions of L. geometricus inhabiting community housing in Samut Songkhram Province. We collected 152 adult spiders between January and August 2017, the majority of which were female (85.53%) and were found on motorcycles (87.50%). Females were much larger than males, with a total body length from the top of the cephalothorax to the bottom of the abdomen of 6.92 ± 0.67 mm, compared with 3.27 ± 0.99 mm in males. In addition, the morphological differences between males and females were significant (p<0.05). Adult females also had a longer life span than males (56.40 ± 11.52 vs. 31.00 ± 2.45 days).The results of this study give us a greater understanding of the biology and morphology of L. geometricus and will be useful for the future monitoring of this species.
Keywords: Morphology; microhabitat use; brown widow spider; Latrodectus geometricus; Thailand